KAJIAN TARIF ANGKUTAN UMUM BERDASARKAN BIAYA OPERASIONAL KENDARAAN (BOK), ABILITY TO PAY (ATP) DAN WILLINGNESS TO PAY (WTP) DI KABUPATEN TTS - Frans, John H.; Messah, Yunita A.; Issu, Nicky T. (Jurnal Teknik Sipil, 2016)
Public transport is being part of human prime need, and also a community transport system, but if we don?t manage it well, it makes problem for the supplier and public transport assessors. This research is to get to know the rate based on the VOC (Vehicle Operational Cost), the Ability To Pay (ATP), and Willingness To Pay (WTP) for the service of public transport in the town of Soe. The observed tract for this public transport is in the Haumeny Terminal to Pasar Inpress Kota Soe, and the New Terminal to Pasar Inpress Kota Soe. The VOC analysis will adapting two kinds of methods, those are from the public work department raisd in year 2005 (Pd.T-15-2005-B) and the method from Directorate General for land transportation number SK.687/AJ.206/DRJD/2002. And for the analysis of ATP and WTP are using the cross tabulation method and travel budget. Trough this research, is known that the real rate is bigger than the counting rate outcome. The real rate is Rp. 3000,00 while the counting rate based on the VOC from the directorate general for land transport is Rp.2205,27 and Rp.1962,14, and for the public work department is Rp. 2621,89 and Rp. 2059,73. The rate for ATP is Rp.2.752,05 and the rate for WTP is Rp. 1.995,50.